2003
DOI: 10.1074/jbc.m305837200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of the Vitamin B12 Metabolism and Regulation in Prokaryotes

Abstract: Using comparative analysis of genes, operons, and regulatory elements, we describe the cobalamin (vitamin B 12 ) biosynthetic pathway in available prokaryotic genomes. Here we found a highly conserved RNA secondary structure, the regulatory B12 element, which is widely distributed in the upstream regions of cobalamin biosynthetic/transport genes in eubacteria. In addition, the binding signal (CBL-box) for a hypothetical B 12 regulator was identified in some archaea. A search for B12 elements and CBL-boxes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
441
1
17

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(479 citation statements)
references
References 50 publications
20
441
1
17
Order By: Relevance
“…Pathways. Upon interrogation of the remaining up-regulated genes, we observed that many have an association with B 12 -dependent metabolism and may be under the control of B 12 riboswitches, known for their ability to modulate transcription of downstream genes dependent on the presence of the B 12 ligand (13,14,(22)(23)(24). Nine putative gene clusters downstream of B 12 riboswitches had elevated expression in Cu-limited conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Pathways. Upon interrogation of the remaining up-regulated genes, we observed that many have an association with B 12 -dependent metabolism and may be under the control of B 12 riboswitches, known for their ability to modulate transcription of downstream genes dependent on the presence of the B 12 ligand (13,14,(22)(23)(24). Nine putative gene clusters downstream of B 12 riboswitches had elevated expression in Cu-limited conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Adenosylcobalamin is known to repress, primarily at the translational level, the expression of a variety of genes involved in B12 synthesis and transport and genes that use B12 as a cofactor (Richter-Dahlfors and Andersson, 1992;Nou and Kadner, 1998), by direct binding of B12 to a conserved RNA structural element, or B12-box, in the 5¢ untranslated region of the gene (reviewed in Vitreschak et al 2003). Rodionov et al (2003) identified B12 elements in the 5¢ untranslated regions of S. coelicolor genes determining B12-independent isozymes of methionine synthase and ribonucleotide reductase. We noted that the unusually long 5¢ untranslated leader sequence of nrdABS contains a B12 structural element, and similar B12 structural elements are present in the upstream regulatory regions of several other Streptomyces genes including those of the metE B12-independent methionine synthase (SCO0985), cobD (SCO01847), the first gene in a large cluster of genes responsible for B12 synthesis, and the cbiNMQO (SCO5961/58), fedDC (SCO7216/17) and ftrDE …”
Section: Complex Regulation Of Class Ia and Class II Rnr Genesmentioning
confidence: 99%
“…The aptamer of each riboswitch class usually is well conserved due to constraints imposed by the ligand binding site. This conservation of aptamer sequences and structures makes bioinformatics analyses of genomic sequences an effective tool for identifying new riboswitch candidates (e.g., Rodionov et al 2002Rodionov et al , 2003Barrick et al 2004;AbreuGoodger and Merino 2005;Corbino et al 2005;Weinberg et al 2007). In contrast, expression platforms may vary considerably and utilize diverse genetic regulatory mechanisms such as transcription termination and translation inhibition (Mandal and Breaker 2004b).…”
Section: Introductionmentioning
confidence: 99%